Faktor-faktor yang mempengaruhi pengungkapan islamic social reporting pada Bank Umum Syariah - Arsyad, Wahidah; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2024)
This research analyses the influence of liquidity, profitability, leverage, company size, and board of commissioners on Islamic social reporting disclosures. This research uses panel data, with a sample size of 10 Sharia Commercial Banks in the 2016-2020 research period. The sampling technique in this research is purposive sampling. The data analysis method uses path analysis. The research results show that liquidity significantly influences the disclosure of Islamic social reporting. Profitability does not have a significant influence on Islamic social reporting disclosure. Leverage does not have a significant effect on Islamic social reporting disclosure. Company size is significantly positive on Islamic social reporting disclosure. Meanwhile, the size of the board of commissioners is not significant to the disclosure of Islamic social reporting.